UI/UX Design Web-Based Learning Application Using Design Thinking Method - Nasution, Winda Suci Lestari; Nusa, Patriot (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
Humans are basically inseparable from education in carrying out life. The implementation and development of educational studies must also be adapted to the conditions and social situations that exist in the community. The main focus of Goal 4 on Sustainable Development Goals (SDGs) is to provide inclusive quality education or to ensure everyone has an equal opportunity to get good quality of education. In fact, Indonesia is still struggling in the quality of teacher issue. In the school year of 2019/2020, there are 8.98% unqualified teachers and headmasters on primary school level, 6.16% on junior high school level, 10.07% on senior high school level, and 10% on vocational high school level. Cumulatively, from primary school level to vocational high school level, there are 247.462 unqualified teachers and headmasters in Indonesia. This is a serious problem, considering that teachers are important component in determining the quality of education itself. In this research, UI/UX design prototype of learning web application named â€œIdeInâ€ was developed using Design Thinking method that consists of empathize, define, ideate, prototype, and test stages. The main focus of this learning web application is to provides an opportunity to the whole community to support education in Indonesia by conducting online classes.